PENERAPAN TEORI CLARK LEONARD HULL DALAM PEMBELAJARAN MATEMATIKA - Ardiansyah Romandhona; Jayanti Putri Purwaningrum (Universitas Muhammadiyah Makassar, 2021)
This study aims to assist teachers in identifying the application of Clark Leonard Hull's theory in mathematics learning. Clark Leonard Hull's theory suggests that biological needs (drive) and the satisfaction of biological needs (drive reduction) are in a central position in all human activities, so that the stimulus ) what happens in learning is almost always associated with biological needs, although the response that comes may take various forms. This theory argues that the learning process occurs due to the Stimulus-Response (SR) interaction. In Hull's theory, the most famous of which is the drive reduction theory which has 4 principles, namely (1) drive, (2) stimulus and response, (3) response, (4) reinforcement. If the Hull theory is applied to mathematics learning activities, it will make students more interested in learning and easily understand the material to be taught by the teacher. In its implementation there are six processes, namely (1) Determination of learning objectives to be achieved, (2) preparation in the process of achieving goals, (3) understanding the environmental situation of the subject to be taught, (4) interpreting the environmental situation based on the understanding obtained, (5) implementation of activities in achieving the goals to be achieved, (6) reflection.